Correction: Shi et al. A Comprehensive Overview of the Antibiotics Approved in the Last Two Decades: Retrospects and Prospects. Molecules 2023, 28, 1762 - Zhenfeng Shi; Jie Zhang; Lei Tian; Liang Xin; Chengyuan Liang; Xiaodong Ren; Min Li (Molecules)
In the original publication [...]